Halal tourism: development, chance and challenge - Eka Dewi Satriana; Hayuun Durrotul Faridah (Universitas Airlangga, 2018)
The tourism sector is one sector that is able to increase employment and increase economic growth. At present, halal tourism is starting to become popular. This is in line with the increase in Muslim tourists from year to year. The development of halal tourism began to be carried out by various countries, muslim and non-muslim countries. This article will explore the development of halal tourism in several countries, reviewing the concepts and principles of halal tourism, and discuss the chances and challenges.